A correction procedure for the working hours variable in the IAB employee history - Philipp vom Berge; Matthias Umkehrer; Susanne Wanger (Journal for Labour Market Research, 2023)
Administrative labour market data for Germany do not contain detailed information on working hours. This poses a serious challenge for many empirical research questions. Between 2010 and 2014, however, it is possible to merge a supplementary data source containing information on working hours reported by employers for each job to the German Social Accident Insurances. One complicating factor is that employers were allowed to report actual working hours, contractual working hours or a full-time worker reference value, and it is not obvious from the data which re-porting scheme was actually used. In this report, we describe this supplementary data source and propose a correction procedure that maps all data entries so that they uniformly reflect contractual working time. After this correction, the distribution of contractual weekly working hours in the combined administrative labour market data closely resembles the distribution from the German Structural Earnings Survey.
Keywords: C80; J30; 330; Administrative labour market data; BeH; Correction procedure; SIAB; Working hours